Case Report: Endovascular repair of thoracoabdominal aneurysm aorta and generalized mycobacterial infection (clinical case) - Chernyavskiy, Mikhail; Vanyurkin, Almaz; Verkhovskaya, Ekaterina; Panteleeva, Yuliya; Ryzhkova, Daria; Basek, Ilona; Ryzhkov, Anton; Mitrofanova, Lubov; Gulyaev, Dmitry; Salogub, Galina; Danilov, Ivan; Ovchinnikov, Dmitry; et al. (Frontiers in Cardiovascular Medicine, 2025)
Mycotic aortic aneurysms account for only 0.7%–1.3% of all aortic aneurysms but remain a life-threatening vascular complication, with in-hospital mortality rates reaching 36%. Immediate surgical intervention is required due to the high risk of rupture. Standard management combines targeted antimicrobial therapy with a radical resection of infected tissues and vascular reconstruction, yet the choice of optimal surgical strategy in elderly, comorbid patients remains controversial. Endovascular interventions are pivotal in the treatment of patients at high risk of infections, offering a minimally invasive approach that reduces the likelihood of complications and improves treatment outcomes. In this study, we report the case of a 65-year-old man who presented with severe lumbar pain. He was diagnosed with mycobacterial spondylitis of the L2–L4 vertebrae and a right-sided psoas abscess secondary to a ruptured thoracoabdominal mycotic aneurysm of 6-month duration. For diagnostic purposes, a right retroperitoneal mass was excised, and a histological examination demonstrated features consistent with mycobacterial infection. Based on these findings, antituberculosis chemotherapy was initiated. Considering the patient's advanced age and comorbidities, branched endovascular aortic repair (BEVAR) was performed as a less invasive alternative to open surgery. This rare clinical case demonstrated the feasibility of BEVAR as a therapeutic option for a ruptured thoracoabdominal aortic aneurysm complicated by disseminated mycobacterial infection and psoas abscess. The successful outcome suggested that BEVAR could serve as an effective alternative to open repair in selected high-risk patients.